2015
DOI: 10.1186/s13002-015-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of medicinal plants to the Gross National Happiness and Biodiscovery in Bhutan

Abstract: BackgroundThe medicinal plants and the associated Bhutanese traditional medicine (BTM) are protected by the country’s constitution and receive both government support and acceptance by the wider public. More than 1000 medicinal plants are described in the BTM but currently collects only 300 species for daily formulations of BTM. These medicinal plants have been one of the drivers of the ‘Gross National Happiness (GNH)’ and biodiscovery projects in Bhutan. However, no review covering the systematic evaluations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 23 publications
0
45
0
1
Order By: Relevance
“…Diverse ecological growing conditions and also altitude ranging from 100 to 7500 m above sea level (masl) favours the growth of diverse kinds of medicinal plants [ 3 ]. These medicinal plants not only play an important role by directly contributing to healthcare system but also serve as primary source of income [ 6 ] thus contributing to Gross National Happiness (GNH) [ 7 ]. Due to its richness in medicinal plants, Bhutan was known as Menjong (land of medicine/medicinal plant) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diverse ecological growing conditions and also altitude ranging from 100 to 7500 m above sea level (masl) favours the growth of diverse kinds of medicinal plants [ 3 ]. These medicinal plants not only play an important role by directly contributing to healthcare system but also serve as primary source of income [ 6 ] thus contributing to Gross National Happiness (GNH) [ 7 ]. Due to its richness in medicinal plants, Bhutan was known as Menjong (land of medicine/medicinal plant) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many medicinal plants contain active secondary metabolites (such as terpenes, flavones, and alkaloids), and are an important source of modern drugs (Wangchuk and Tobgay, 2015 ). You-You Tu, the mother of artemisinin, was awarded Nobel Prize in medicine in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…These practices would eventually deplete the MP resources of Tshothang Chiwog. Other workers also reported that MPs in some localities of Bhutan have been shrinking over the years (e.g., Wangchuk and Tobgay, 2015). Rai et al (2000) and Muraleedharan et al (2005) also reported that overexploitation is a principal reason for the shrinking non-wood forest product resources in Sikkim Himalayas and Western Ghats of India, respectively.…”
Section: Ethnobotanical and Socioeconomic Aspectsmentioning
confidence: 99%